Pengaruh Pelatihan Ketrampilan Regulasi Emosi untuk Meningkatkan Kemampuan Coping Stres Orang tua yang Memiliki Anak dengan Riwayat Gangguan Skizofrenia - Pahlevi, Jefri Reza; , Dr. Sri Lestari, M.Si., Psikolog; , Setia Asyanti, M.Si., Psikolog (2016)
Parents who have children with schizophrenia get a lot of pressure,physically anda emotionally. Parents are supposed to stay calm and patient in taking car of their children. Unfortunately due to negative emotions, parents behave in less supportive way toward chilldren's rehabilitation; such as yelling, screaming, slapping, neglecting, even locking children in a room. Therefore, parents must develop decent emotion reulation skill in order to monitor emotions regulation skill in order to monitor emotions, evaluate negative emotions, modify negative emotions positive, and channel emotions into positive expression so that adaptive coping stress can be obtained. This research aimed to test if there was an influence of emotion regulation training in improving adaptive coping stress of parents who have children with schizophrenia. Subjects were 12 patients chosen by nonprobability sampling, which were divided into 2 groups; 6 subject belonged to experimential group, and 6 subjects belonged to control group. Subjects were chosen based on these criteria: parents are 45-50 y.o with minimum education of Junior High School, are biological parents of the child, have a 7-18 y.o child with schizophrenia who has been hospitalized for more than once. Coping stress of parents was measured using coping stress scale(Snyder and Gomez, 2005). Data were analyzed using SPSS 19 analysis using Wilcoxon Paired T-test resulted in significance sciere of p= 0,027 (p < 0,05); which showed improvements in parents coping stress after emotion regulaiton training.